Reparation as a veritable tool for redressing women's reproductive rights violations in armed conflicts in Nigeria (2017)
In recent times, there has been a remarkable increase in armed conflicts particularly those that are non- international in character. Of the armed conflicts that have taken place since World War II, ninety percent have taken place in developing countries with sub-Saharan African countries experiencing more conflicts than any other region in the world. On most occasions, women and children have been the most affected with various human rights violations and sexual violence crimes. Of these crimes, rape and indecent assault have been the most reported. Judicial systems have often been inadequate in addressing most of these crimes. This article therefore proposes reparations for victims of rape using a transitional justice framework. This article adopts a desk review approach of extant literature on the subject matter. It also relies on field survey reports on the state of armed conflicts globally and in Nigeria. The article identifies the nature of violations of women's reproductive rights and how these impact on their health and well-being. It explores the options of reparations as a means of redressing these violations. In doing so, the article undertakes a comparative approach by examining experiences from Sierra Leone where there were massive violations during conflict from 1991 to 2002. This article exposes the possible challenges associated with adopting reparations mechanism in Nigeria and concludes that, for promoting access to justice in Nigeria, adequate funding and political will have to be in place to ensure sustainability.